Efek Program “Mindful Parenting” terhadap Perubahan Stres Pengasuhan Orang Tua Tunggal yang Memiliki Anak dengan Disabilitas Ganda - Nurhamidah Nurhamidah; Sofia Retnowati (Faculty of Psychology, Universitas Gadjah Mada, 2018)
Distress in parenting can cause a parent’s emotional reactions, perceptual bias, and influence negative parenting behavior. The purpose of this study was to determine the effect of the Mindful Parenting Program on the parenting stress changes of single-parent whom parenting a child with multiple disabilities. The single-subject design was used in this study by considering the unique characteristics of the individual participant. The research data were obtained using stress parenting scale, mindful parenting scale, daily self-report, observation, and interview. The results showed the effect of the Mindful Parenting Program that was emerged only temporary changes in stress parenting of single-parent whom parenting a child with multiple disabilities. The participant experiences a temporary increase of mindful parenting skills that showed the changes in participant’s awareness of physical sensation, emotions, thoughts, and parenting behavior which related to the changes in parenting stress. Further research’s needed.